TABOO EXPRESSIONS IN ASAHAN MALAY: AN ETHNOLINGUISTIC APPROACH - Sari, Etika; Mulyadi, Mulyadi; Zulfan, Zulfan (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
This research aims to classify taboo language expressions in Asahan Malay. The phenomenon of taboo language is important to study as an effort to maintain local wisdom. This research used a qualitative method with an ethnolinguistic approach. The location of this research is in Tanjungbalai, North Sumatera. The research data comes from the speech of native Asahan Malay speakers, research instruments in the form of interview guides, recordings and field notes. The data collection method is the field observation method. The results of the research show that there are two types of taboo expressions in Asahan Malay. The first one is general taboo, namely words that are lexically classified as taboo because they include words related to sex (15 data), bodily waste (7 data), cursing or cursing (9 data) as well as insults and demeaning (26 data), while the second one is special taboo, namely words that are not literally/lexically taboo but are considered taboo by Asahan Malay speakers because they are interpreted from a cultural perspective, namely consisting of words that are considered to bring harm (10 data) and are considered impolite (1 data).